THE USE OF JIGSAW IN TEACHING READING FOR JUNIOR HIGH SCHOOL STUDENTS : QUASI-EXPERIMENTAL RESEARCH OF THE FIRST GRADE STUDENTS OF SMPN 2 MAJALENGKA - Saadatul Wida Adawiyah, - (2009)
This research was aimed to investigate the use of jigsaw technique particularly in teaching reading for junior high school students in SMPN 2 Majalengka. This research was conducted by using a quasi-experimental design. The non-equivalent control group design was chosen because it allowed the use of experimental and control groups. Therefore, two classes were selected to be sample of this research, one class as the control group and one class as the experimental group. There were 36 students in each class. The treatment was given in six sessions. Reading comprehension tests were used as the research instrument. The experimental research used two kinds of tests; namely pretest and posttest. Then, the scores of each test were analyzed by using independent t-test. Based on the scores of independent t-test and effect size, it can be concluded that there was a significant difference in both groups. Experimental group students have a higher reading score (M =75.56, SE = 2.087) than control group students (M = 65.14, SE = 1.809). This difference is very significant t (70) = 3.771, p < .05; with the large effect size r = .4109. It indicated that the students' reading achievement in both groups was totally different. In addition, the students' responses through the given questionnaire also showed that jigsaw provided some advantages for students in learning reading. In other words, the t-test and questionnaire analysis showed that the jigsaw technique was effective to develop students' reading ability.